Strategi Transformasi Kualitas Laporan Keuangan Pemerintah Daerah - Widodo, Sri; Sari, Monika Kurnia; Handono, Wiyasto Dwi (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
Local governments are one of the government entities that must continue to strive to improve transparency and accountability in financial management to realize good governance. The purpose of the study was to determine the effect of government accounting standards, human resource competence, and the use of information technology on the quality of financial statements of the local government of Yogyakarta City. This type of research is quantitative research with sampling using purposive sampling methods with certain criteria. The hypothesis testing tool uses SPSS. The results of this study prove that the application of appropriate government accounting standards, as well as increasing investment in the quality of adequate human resources, and optimal use of technology can improve the quality of local government financial statements in Yogyakarta City. The implication of this research is that the improved quality of local government financial statements assists government entities in optimizing financial management to meet the needs of the community.